Specialized Brains Performing Specialized Tasks: Beta/Gamma Eeg Non-Linear Analysis Reveals Discriminative Differences Between the Chaos/No-Chaos Content of Specialized Brain S Dynamics - Cordova-Gonzalez, F; Palominos-Villavicencio, F; Canete-Arratia, L; Troncoso-Martinez, N (Elsevier B.V., 2016)
We studied and compared different non-linear features of the human EEG in the context of the search and characterization of specific functional fingerprints of the EEG dynamics that allow differentiating behaviorally recognized specialized professional activities. Sets of EEG data obtained from two groups of professional performers, a group of 10 professional modern dancers and a group of 12 professional chopper pilots, were compared while executing a mental-cognitive task related to their professional specialty. Dancers were asked to use mental imagination to plan choreographic movements and pilots were asked to solve a reduced version of the Raven s matrices visual intelligent test. Both tasks were analyzed during the first two minutes while EEG activity was recorded from 14 mastoid bone referenced electrodes using the brain-computer interface Emotiv® Epoc Research Edition, sampling at 128 Hz rate. Dancers and pilots were then compared in term of their long- and short-term Hurst (H) exponent estimation for beta and gamma EEG ranges. We found that non-linear estimation of chaos in the EEG time series allows differentiating between the brain functional strategies employed by differently specialized groups of performers. The group of pilots showed higher estimated H values for the beta band than for gamma band, contrary to what we found for dancers in which estimated H for gamma band showed higher values than for beta range. © 2016 The Author(s).